2007
DOI: 10.1073/pnas.0701762104
|View full text |Cite
|
Sign up to set email alerts
|

Energy transport in peptide helices

Abstract: We investigate energy transport through an ␣-aminoisobutyric acid-based 310-helix dissolved in chloroform in a combined experimental-theoretical approach. Vibrational energy is locally deposited at the N terminus of the helix by ultrafast internal conversion of a covalently attached, electronically excited, azobenzene moiety. Heat flow through the helix is detected with subpicosecond time resolution by employing vibrational probes as local thermometers at various distances from the heat source. The experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
331
5
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(358 citation statements)
references
References 45 publications
21
331
5
1
Order By: Relevance
“…Since in the parametrization of our model we used the fluctuations of the vibrational constants in NMA-d 7 in heavy water, we probably overestimated the importance of the fast water dynamics: the surrounding of the amide groups in a helix is somewhat less dominated by water than in a single NMA-d 7 molecule. In addition, our approach neglects the role of slow conformational changes in the helix; at least for short helices such changes have been seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in the parametrization of our model we used the fluctuations of the vibrational constants in NMA-d 7 in heavy water, we probably overestimated the importance of the fast water dynamics: the surrounding of the amide groups in a helix is somewhat less dominated by water than in a single NMA-d 7 molecule. In addition, our approach neglects the role of slow conformational changes in the helix; at least for short helices such changes have been seen.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the analogues of the NOESY variant of 2DNMR allow for the study of dynamics, because they involve a waiting time t 2 that may be controlled at the femtosecond time scales, thus allowing one to take snapshots of a system while it evolves. 2,3 Examples of systems that have been studied using 2DIR or 2Dvis spectroscopies with nonzero waiting times include relatively simple few-level systems, such as the coupled amide I and amide II vibrations in N-methylacetamide (NMA) 4 and vibrations in other small organic molecules, 5 as well as extended systems with a multitude of levels, such as the amide I band in polypeptides or proteins, 6,7 the excitonic transitions in the photosynthetic Fenna-Matthew-Olsen complex, 8 and the excitonic transitions in double-wall molecular nanotubes. 9 In the simplest situation, with only two interacting vibrational or electronic states of interest, it is rather straightforward to obtain information about their coupled dynamics from the waiting time dependence of the 2D spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…5 Chemical and photochemical reactions occurring at specific spots in biomolecules can result in large increases in temperature in very small volumes. Transient photon experiments, where photon absorption is converted to vibrational energy, show that the temperature rise resulting from this process can be very significant, between 500 and 1000 K. 6,7 Recent work on the Ca 2+ -ATPase embedded in the sarcoplasmic reticulum has suggested that this enzyme can -under working conditions -release significant amounts of heat. Using micro-thermometers it was found that thermal gradients of the order of 10 5 K/m can develop between regions separated by tens of micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…As in our previous studies [15][16][17][18] the isotope labels are placed by incorporating 13 C-l-Ala, since this amino acid is readily available commercially and does not destabilize the 3 10 -helix significantly. An urethane moiety was inserted between the linking group and the actual peptide to have an intrinsically spectrally resolved C=O group at the beginning of the helical chain.…”
mentioning
confidence: 99%